Independensi Peradilan: Studi Kritis Terhadap Hakim Pengadilan Negeri Surabaya Yang Memberikan Putusan Dalam Kasus Ronald Tannur - Haikal, M. Surya; Amarini, Indriati (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
As a state governed by the rule of law, Indonesia requires an independent judiciary capable of upholding justice objectively and free from external influence. However, the Ronald Tannur case exposes significant shortcomings in the implementation of judicial independence, marked by allegations of bribery and external pressures on the presiding judge. This study critically examines the extent to which judicial independence was maintained in the handling of the case and evaluates its implications for public trust in the legal system. Using a normative juridical approach, the research analyzed several legal frameworks, including Law No. 48 of 2009 on Judicial Power, Law No. 49 of 2009 (Second Amendment to Law No. 2 of 1986 on General Courts), the 2009 Joint Decree of the Supreme Court and the Judicial Commission on the Code of Ethics for Judges, as well as court decisions: Surabaya District Court Decision No. 454/Pid.B/2024/PN.Sby and Supreme Court Cassation Decision No. 1466 K/Pid/2024. The findings indicate that judicial independence in this case was undermined by suspected corruption, socio-political pressure, and inadequate institutional oversight. The initial acquittal at the district court levellater overturned by the Supreme Courtreflects a breach of judicial integrity and fundamental justice. This case underscores the urgent need for stronger judicial oversight mechanisms, ethical reforms, and a firm commitment to the separation of powers in order to uphold the rule of law transparently and equitably. Ultimately, the Ronald Tannur case serves as a crucial turning point in efforts to restore public confidence and reform the Indonesian judicial system. Keywords: Judicial Independence, Judiciary, Supremacy of law.